Analysis of the influence of heat transfer on the stationary operation and performance of a solid oxide fuel cell/gas turbine hybrid power plant. (1st February 2018) - Steilen, Mike; Saletti, Costanza; Heddrich, Marc P.; Friedrich, K. Andreas
Highlights: Heat losses from components are included to improve prediction of operating range. Adiabatic assumption underestimates high power operating range by 10%. Adiabatic assumption overestimates electrical efficiency by 4 percent points. Power output can be modulated to 30% by adjusting the SOFC operating temperature. Electrical efficiency (HHV) higher than 0.55 is maintained throughout the range. Abstract: Hybrid power plants consisting of solid oxide fuel cells (SOFC) and a gas turbine (GT) can play an essential role in the future energy scenario due to the expected high electrical efficiency, fuel flexibility and good part-load performance. A demonstration SOFC/GT hybrid power plant is being setup in Stuttgart with state of the art, commercially available electrolyte supported cell (ESC) stacks and its operation is being simulated by means of a overall system model. However, the model used in this paper, in contrast to most models in literature, accounts for heat transfer based on actual geometries and materials. In the present study, the system model is integrated with a set of sub-models that predict the heat losses of the components of the hybrid power plant with a feasible computational speed. This allows for an improved prediction of the operating range as well as for the prevention of undesired operating conditions. The results of the simulations of the stationary operation of the hybrid power plant with varying heat losses are shown and discussed. Operating limitations are analyzed as well as system performance. It is shown that it is possible to operate the hybrid power plant from design power output to 30% of it. A system electrical efficiency higher than 0.55 considering the fuel's higher heating value is maintained throughout the entire range. Further design choices and developments could lead to an improvement of this condition. In addition, an adiabatic assumption can lead to about 4 percentage points overestimation of electrical efficiency and reduces the high power operating range by about 10%. This approach opens up a new perspective on the simulation of this type of power plant.